OP0029 Clinical effect of vedolizumab on articular manifestations in patients with spondyloarthritis associated with inflammatory bowel disease. (12th June 2018) - Paccou, J.; Nachury, M.; Duchemin, C.; Desreumaux, P.; Flipo, R.-M.; Pariente, B.
Abstract : Background: Data on the effects of vedolizumab on joint manifestations remain controversial. 1, 2 Objectives: The purpose of this study was to 1 evaluate baseline characteristics of crohn's disease (CD) and ulcerative colitis (UC) patients treated with vedolizumab, 2 assess the effect of vedolizumab on joint manifestations in patients with inflammatory bowel disease (IBD)-associated Spondyloarthritis (SpA), and 3 evaluate new onset of SpA under VDZ. Methods: This single-centre, retrospective and observational study was conducted from July 2014 to July 2017. The charts of all patients with IBD who had undergone treatment with vedolizumab for more than 3 months were reviewed. The patients' demographic and clinical characteristics were collected. Data on IBD-associated SpA were collected as well as new onset of SpA under VDZ. The ASAS criteria were used to establish the diagnosis of SpA. Results: Patient characteristics and main results are shown in table 1. A total of 171 patients diagnosed with IBD were treated with vedolizumab from July 2014 to July 2017. Notably, 97.1% of patients had been previously treated with at least one TNF-α inhibitor. All patients included in this study completed the induction phase at last observation, and the mean follow-up of the entire cohort was 14.3±12.0 months. Ten (5.8%) patients had a history of IBD-associated SpA but were in clinical remission at the time of initiation of VDZ, whereas 4 (2.4%) had active SpA when VDZ was started. First, no clinical benefit on SpA following initiation of VDZ was found in those 4 patients with active SpA. Second, exacerbation of SpA in patients with clinical remission at initiation of VDZ was found in 6/10 patients whereas no effect was reported in the remaining 4/10 patients. All those 14 patients with IBD-associated SpA were under TNF inhibitors just before starting VDZ. Finally, new onset of SpA induced by VDZ was reported in 1 patient. Conclusions: Vedolizumab does not seem to show any efficacy in IBD-associated SpA and might even induce exacerbation or new onset of SpA. Inception cohort studies are needed to better evaluate the effect of vedolizumab on joint manifestations. References: [1] Varkas G, Thevissen K, De Brabanter G, et al. Ann Rheum Dis2017May;76(5):878–881. [2] Orlando A, Orlando R, Ciccia F, et al. Ann Rheum Dis2017Sep;76(9):e31. Disclosure of Interest: None declared